Enterovirus Replication Organelles and Inhibitors of Their Formation - Li, Xinhong; Wang, Mingshu; Cheng, Anchun; Wen, Xingjian; Ou, Xumin; Mao, Sai; Gao, Qun; Sun, Di; Jia, Renyong; Yang, Qiao; Wu, Ying; Zhu, Dekang; et al. (Frontiers in Microbiology, 2020)
Enteroviral replication reorganizes the cellular membrane. Upon infection, viral proteins and hijacked host factors generate unique structures called replication organelles (ROs) to replicate their viral genomes. ROs promote efficient viral genome replication, coordinate the steps of the viral replication cycle, and protect viral RNA from host immune responses. More recent researches have focused on the ultrastructure structures, formation mechanism, and functions in the virus life cycle of ROs. Dynamic model of enterovirus ROs structure is proposed, and the secretory pathway, the autophagy pathway, and lipid metabolism are found to be associated in the formation of ROs. With deeper understanding of ROs, some compounds have been found to show inhibitory effects on viral replication by targeting key proteins in the process of ROs formation. Here, we review the recent findings concerning the role, morphology, biogenesis, formation mechanism, and inhibitors of enterovirus ROs.